2015
DOI: 10.1007/s10096-015-2337-6
|View full text |Cite
|
Sign up to set email alerts
|

TBX21 polymorphisms are associated with virus persistence in hepatitis C virus infection patients from a high-risk Chinese population

Abstract: Hepatitis C virus (HCV) infection is a major cause of chronic liver disease and the varied outcomes of the infection depend on both viral and host factors. We have demonstrated that the HCV alternate reading frame protein (F protein) is related to Th1/Th2 bias which is involved in virus persistence in chronic hepatitis C (CHC) patients. The purpose of this study was to test the hypothesis that genetic variants of TBX21 (T cell specific T-box transcription factor) were associated with the outcomes of HCV infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Correlation of genetic polymorphism has also been extensively studied in non-malignant diseases, as well as malignant diseases, and interestingly, were found to carry strong associations (18,20). According to the results of our study, there is no definitive evidence that laryngeal cancer is influenced by the polymorphisms of GLUT1, HIF1α, and TBX21.…”
Section: Discussionmentioning
confidence: 47%
“…Correlation of genetic polymorphism has also been extensively studied in non-malignant diseases, as well as malignant diseases, and interestingly, were found to carry strong associations (18,20). According to the results of our study, there is no definitive evidence that laryngeal cancer is influenced by the polymorphisms of GLUT1, HIF1α, and TBX21.…”
Section: Discussionmentioning
confidence: 47%
“…Several studies have reported that enriched genes such as STAT5B (Mukherjee et al 2014), SOCS1 (Zheng et al 2015), CCR1 (Miller et al 2006) and CCL5 (Sali mi et al 2017) were highly expressed in respiratory syncytial virus infection, but elevated expression these genes may be involved in development of SARS-CoV-2 infection. Increasing evidence shows that the enriched genes such as IFNAR2 (Romporn et al 2013), TBX21 (Zhu et al 2015), GBP1 (Anderson et al 1999), IRF5 (Vandenbroeck et al 2011) and IFI35 (Estrabaud et al 2015) were over expressed in various viral infections, but high expression of these genes may be involved in infection of SARS-CoV-2 infection. Novel biomarkers such as IKBKE (inhibitor of nuclear factor kappa B kinase subunit epsilon), TP53, CD247, IL18RAP, IL18R1, HRAS (HRas proto-oncogene, GTPase), PSMB9, IKBKB (inhibitor of nuclear factor kappa B kinase subunit beta), ITGB2 and LTB4R were highly expressed and might be involved in progression of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%